(untitled) (Anclajes, 2025)
Los miedos (1963) is a novel by Eduardo Blanco Amor (1897-1979), a bilingual writer in Galician and Spanish who lived for decades in Argentina, where he developed the first part of his literary career cultivating various genres. This article examines the process of creation and subsequent trajectory of the novel, with which Blanco Amor intended to position himself in the Spanish literary circles as a resident of Argentina, where he had settled in 1965, and whose diverse conditions had a great impact on an author separated from his native space. This article deals with the circumstances related to the audacious participation of Los miedos in the 1961 Nadal Prize, in which Blanco Amor was a finalist, to the eventful publication of the work by the Destino publishing house and, finally, to the serious problems that the volume suffered with Francoist censorship.